MELT EVOLUTION DURING THE CRYSTALLIZATION OF BASANITES OF THE TERGESH PIPE, NORTHERN MINUSINSK DEPRESSION - Timina T.Yu.; Sharygin V.V.; Golovin A.V. (My University, 2006)
In this paper we describe the mineralogy and geochemistry of and melt inclusions in minerals from the Tergesh pipe, northern Minusinsk Depression. The rocks are composed of olivine and clinopyroxene phenocrysts and a groundmass of olivine, clinopyroxene, titanomagnetite, plagioclase, apatite, ilmenite, and glass. Melt inclusions were found only in the olivine and clinopyroxene phenocrysts. Primary melt inclusions in olivine contain glass, rhönite, clinopyroxene, a sulfide globule, and low-density fluid. The phase composition of melt inclusions in clinopyroxene is glass + low-density fluid ± xenogenous magnetite. According to thermometric investigations, the olivine phenocrysts began crystallizing at T = 1280-1320°C and P > 3.5 kbar, whereas groundmass minerals were formed under near-surface conditions at T< 1200°C. The oxygen fugacity gradually changed during basanite crystallization from oxidizing (NNO) to more reducing conditions (QFM). The investigation of glass compositions (heated and unheated inclusions in phenocrysts and groundmass) showed that the evolution of a basanite melt during its crystallization included mainly an increase in SiO2, Al2O3, and alkalis, while a decrease in femic components, and the melt composition moved gradually toward tephriphonolite and trachyandesite. Geochemical evidence suggests that the primary basanite melt was derived from a mantle source affected by differentiation. © Pleiades Publishing, Inc. 2006.
Keywords: basanites